Condensation and Precipitation of Water Vapor: The Emergence of a Precursor Model through the Engineering Design Process - Michalis Ioannou; George Kaliampos; Konstantinos Ravanis (MDPI AG, 2024)
Early Childhood Science Education, within a wide range of research topics, studies mental representations of children aged 3-8 years about natural phenomena. Recently, there has been a strong scientific interest in the way children construct precursor mental models. The current study attempts to address children's mental representations of clouds, as well as condensation and the precipitation of water vapour. To fulfill this goal, a qualitative study was implemented involving 19 preschool children. Specifically, the survey included pre-tests and post-tests for recording children's mental representations, as well as a structured teaching process. The main activities of this teaching process followed the four stages of the Engineering Design Process and a STEAM approach, adapted both to children's cognitive needs and the conditions of a real classroom. The results showed that most children of this age (mean age: 5.05 years) were able to approach the concepts of condensation and precipitation, as well as the process of cloud creation. It seems, therefore, that it is possible for young children's initial mental representations to be transformed into representations compatible with school knowledge. Finally, the data and the results of the research lead to the conclusion that children of this age are capable of constructing a precursor model about clouds and the phenomena of condensation and precipitation.